Information retrieval for systematic reviews in food and feed topics: A narrative review. (7th February 2018) - Wood, Hannah; O'Connor, Annette; Sargeant, Jan; Glanville, Julie
Abstract : Introduction: Systematic review methods are now being used for reviews of food production, food safety and security, plant health, and animal health and welfare. Information retrieval methods in this context have been informed by human health‐care approaches and ideally should be based on relevant research and experience. Objective: This narrative review seeks to identify and summarize current research‐based evidence and experience on information retrieval for systematic reviews in food and feed topics. Methods: MEDLINE (Ovid), Science Citation Index (Web of Science), and ScienceDirect (http://www.sciencedirect.com /) were searched in 2012 and 2016. We also contacted topic experts and undertook citation searches. We selected and summarized studies reporting research on information retrieval, as well as published guidance and experience. Results: There is little published evidence on the most efficient way to conduct searches for food and feed topics. There are few available study design search filters, and their use may be problematic given poor or inconsistent reporting of study methods. Food and feed research makes use of a wide range of study designs so it might be best to focus strategy development on capturing study populations, although this also has challenges. There is limited guidance on which resources should be searched and whether publication bias in disciplines relevant to food and feed necessitates extensive searching of the gray literature. Conclusions: There is some limited evidence on information retrieval approaches, but more research is required to inform effective and efficient approaches to searching to populate food and feed reviews.